Off-pump versus on-pump coronary artery bypass grafting in patients with chronic obstructive pulmonary disease - Karim Mohamed Mady; Amr Ahmed Abdou Ettish; Wael Mohamed Elfeky; Mohamed Mostafa Abdelaal (Journal of the Pakistan Medical Association, 2023)
N/A